Appropriateness of antibiotic use and mortality risk factors in moderate to severe COVID-19 patients admitted to the intensive care unit of Bali Mandara Hospital in 2021 - Saputra, I Wayan Agus Gede Manik; Laksana, Ngurah Putu Werda; Idayanti, Luh Gede Dewi; Shantivani, Made Intan; Yuliastini, Ni Luh Putu; Pratama, I Putu Agus Bayu; Laksana, Ida Ayu Candrika Widyasari (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2025)
Introduction: The COVID-19 pandemic has been closely linked to the overuse of antibiotics, particularly in hospitalized patients. Early clinical uncertainty and lack of definitive treatments led to widespread empiric use. This study assessed the appropriateness of antibiotic use and identified mortality risk factors among moderate to severe COVID-19 patients in Bali Mandara Hospital's ICU. Methods: A retrospective cross-sectional study of 72 moderate to severe COVID-19 patients was conducted from 200 ICU admissions in 2021. Simple random sampling was used. Antibiotic appropriateness was assessed using the Gyssens method. Variables such as age, sex, severity, comorbidities (hypertension, diabetes), and culture results were analyzed using Chi-square tests. Result: Among 322 antimicrobials, 226 were antibiotics. Gyssens' classification showed 40% appropriate use and 60% inappropriate use, mainly due to lack of indication (Category V). Age over 60, sex, and disease severity were significantly associated with mortality (p<0.05). Bacterial co-infection was confirmed in 30.6%, predominantly Enterobacteriaceae. Conclusion: Antibiotic appropriateness remains low, with substantial overuse. Mortality correlated significantly with age, sex, and disease severity. These findings underscore the need for enhanced antimicrobial stewardship and targeted clinical management in cases of severe COVID-19.